Finding of vanadium-bearing garnet from the Sor Rondane Mountains, East Antarctica - Yasuhito Osanai; Teiichi Ueno; Noriyoshi Tsuchiya; Yuhei Takahashi; Yoshiaki Tainosho; Kazuyuki Shiraishi (National Institute of Polar Research, 1990)
Vanadium-bearing green garnets have been found in the Menipa mountain mass, central part of the Sor Rondane Mountains, East Antarctica. These garnets are the main constituent minerals of granulite-facies metamorphosed graphite-bearing calcareous metapelite. They show three types of mode of occurrence as follows; i) large porphyroblast (type-1), ii) fine crystal (type-2) in kelyphite rim around type-1 garnet, and iii) fine-grained porphyroblast (type-3) in matrix. These three types of vanadium-bearing garnets exhibit distinct characters in chemical compositions. The V^, Cr^ and Fe^ contents in these garnets increase from type-1 to type-3 through type-2 with increasing consistency of green color, while the Cr_2O_3/V_2O_3 and Fe_2O_3/V_2O_3 ratios are constant. Therefore, the form of cation substitution in vanadium-bearing garnets is shown as 4V^, (Cr^, Fe^)⇋5Al^. Modes of occurrence and chemical characteristics of vanadium-bearing green garnets are described here, and physical properties of these garnets are also examined.